2008
DOI: 10.1097/01.ncn.0000304777.48155.e3
|View full text |Cite
|
Sign up to set email alerts
|

Intentions of Hospital Nurses to Work With Computers

Abstract: The purpose of this study was to determine registered nurses' attitudes related to intent to use computers in the hospital setting as a predictor of their future behavior. The study was further aimed at identifying the relationship between these attitudes and selected sociological, professional, and personal factors and to describe a research model integrating these various factors. The study was based on the theory of planned behavior. A random sample of 411 registered nurses was selected from a single large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 15 publications
4
54
0
1
Order By: Relevance
“…Shoham and Gonen 15 found that nurses experienced with use of computers have more positive attitudes toward the use of computers than those of the inexperienced ones. The present study's result is consistent with the findings of Bongartz 36 and Shoham and Gonen, 15 who found that nurses exposed to computers showed more positive attitudes toward computers. Contrary to the present study, Sultana 32 found no significant differences in terms of attitudes toward computers among subjects categorized into different groups by their present computer experience, that is, less than 1, 1, 2, 3, 4, and 5 years.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…Shoham and Gonen 15 found that nurses experienced with use of computers have more positive attitudes toward the use of computers than those of the inexperienced ones. The present study's result is consistent with the findings of Bongartz 36 and Shoham and Gonen, 15 who found that nurses exposed to computers showed more positive attitudes toward computers. Contrary to the present study, Sultana 32 found no significant differences in terms of attitudes toward computers among subjects categorized into different groups by their present computer experience, that is, less than 1, 1, 2, 3, 4, and 5 years.…”
Section: Discussionsupporting
confidence: 95%
“…Several studies have been conducted worldwide to examine nurses' attitudes toward use of computers and factors affecting their attitudes. [4][5][6][7][9][10][11][12]14,15,[26][27][28][29][30][31][32] However, the number of such studies in Turkey is limited. 25,33 Therefore, the present study was performed with the purpose of identifying the attitudes of Turkish nurses toward the utilization of computers in healthcare and factors affecting their attitudes.…”
Section: Factors Affecting Nurses' Attitudes Toward Computers In Healmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies had obtained a response rate between 23% and 84%. 12,27,28 For this study, we anticipated a response rate of 50%. At the time of the study, a total of 199 nurses worked in the CSSS, so this number constituted the target population for the study.…”
Section: Settingmentioning
confidence: 99%